Pengaruh Tenaga Kerja dan Teknologi terhadap Pendapatan melalui Modal sebagai Variabel Intervening UMKM Coffee Shop di Kota Medan - Adhani, Nadia; Ruslan, Dede; Sari, Raina Linda (Economic Reviews Journal, 2024)
A business that is growing rapidly in the city of Medan is the emergence of coffee shops. Coffee shop visitors do more than just taste coffee; they also use the space for casual gatherings. It is hoped that the coffee shop business in Medan City will have a positive impact on the development of the city, especially in the economic and tourism sectors. The coffee shop business has the potential to increase community income, employment, tourism and coffee production in the city of Medan. The current emergence of coffee shops cannot be separated from the influence of the big city lifestyle which offers lots of fun for entertainment seekers and has become a favorite "hang out" place for young people in campus areas, shopping centers and offices in the city of Medan. The phenomenon of the presence of a new trend in drinking coffee is actually not much different from drinking coffee in a traditional coffee shop. This research aims to determine the influence of Labor and Technology on Income through Capital as an intervening variable for coffee shop in the city of Medan. This research is a descriptive and quantitative analysis, the sample in this research is 50 respondents who are coffee shop owners in the city of Medan and the data analysis technique used to test the hypothesis is a quantitative analysis technique, which is a way of analyzing data using statistical tools such as SPSS 21.0. The research results show that the variable Labor has a positive and significant effect on income, Technology has a positive and significant effect on income, Labor has a positive and significant effect on capital, Technology has a positive and significant effect on capital, Capital has a positive and significant effect on income, Labor has an effect positive and significant on income through capital as an intervening variable. Technology has a positive and significant effect on income through capital as an intervening variable.